'Mechanical restraint—confounders, risk, alliance score': testing the clinical validity of a new risk assessment instrument. (18th August 2017) - Deichmann Nielsen, Lea; Bech, Per; Hounsgaard, Lise; Alkier Gildberg, Frederik
Abstract: Background: Unstructured risk assessment, as well as confounders (underlying reasons for the patient's risk behaviour and alliance), risk behaviour, and parameters of alliance, have been identified as factors that prolong the duration of mechanical restraint among forensic mental health inpatients. Aim: To clinically validate a new, structured short-term risk assessment instrument called the Mechanical Restraint–Confounders, Risk, Alliance Score (MR-CRAS), with the intended purpose of supporting the clinicians' observation and assessment of the patient's readiness to be released from mechanical restraint. Methods: The content and layout of MR-CRAS and its user manual were evaluated using face validation by forensic mental health clinicians, content validation by an expert panel, and pilot testing within two, closed forensic mental health inpatient units. Results: The three sub-scales (Confounders, Risk, and a parameter of Alliance) showed excellent content validity. The clinical validations also showed that MR-CRAS was perceived and experienced as a comprehensible, relevant, comprehensive, and useable risk assessment instrument. Conclusions: MR-CRAS contains 18 clinically valid items, and the instrument can be used to support the clinical decision-making regarding the possibility of releasing the patient from mechanical restraint. Implications: The present three studies have clinically validated a short MR-CRAS scale that is currently being psychometrically tested in a larger study.